Water as Sacrament: Tillich, Gender and Liturgical Eco‐Justice. (June 2014) - Guðmarsdóttir, Sigríður
Abstract Theological operations of language that turn physical water into figurative and textual logos‐water are examined in the article with the help of Tillich´s "Nature and Sacrament, " where Tillich reflects the actual relationship between water and word in the sacrament of baptism. Moving to the ecological struggles of contemporary life, the article ponders the scarcity of water in the ecological struggle, and finally the gender implications of figurative water operations.